Flipping the Dental Anatomy Classroom - Sergio Varela Kellesarian (MDPI AG, 2018)
The development of cognitive knowledge, motor skills, and artistic sense in order to restore lost tooth structure is fundamental for dental professionals. The course of dental anatomy is taught in the initial years of dental school, and is a component of the basic core sciences program in the faculties of dentistry. The learning objectives of the dental anatomy course include identifying anatomical and morphological characteristics of human primary and permanent teeth; identifying and reproducing tooth surface details in order to recognize and diagnose anatomical changes; and developing student’s psychomotor skills for restoring teeth with proper form and function. The majority of dental schools rely on traditional methods to teach dental anatomy, using lectures to convey the theoretical component; whereas the practical component uses two-dimensional drawing of teeth, identification of anatomical features in samples of preserved teeth, and carving of teeth. The aim of the present literature review is to summarize different educational strategies proposed or implemented to challenge the traditional approaches of teaching dental anatomy, specifically the flipped classroom educational model. The goal is to promote this approach as a promising strategy to teaching dental anatomy, in order to foster active learning, critical thinking, and engagement among dental students.